Powerful combination of g-C3N4 and LDHs for enhanced photocatalytic performance: A review of strategy, synthesis, and applications - Song, Biao; Zeng, Zhuotong; Zeng, Guangming; Gong, Jilai; Xiao, Rong; Ye, Shujing; Chen, Ming; Lai, Cui; Xu, Piao; Tang, Xiang (Advances in colloid and interface science, 2019)
The utilization of solar energy with photocatalytic technology has been considered a good solution to alleviate environmental pollution and energy shortage. Constructing 2D/2D heterostructure photocatalysts with layered double hydroxide (LDH) and graphitic carbon nitride (g-C3N4) is an effective approach to attain high performance in solar photocatalysis. This paper provides a review of recent studies about 2D/2D LDH/g-C3N4 heterostructure photocatalysts. Main strategies for constructing the desired 2D/2D heterojunction are summarized. The planar structure of LDH and g-C3N4 offers a shorter transfer distance for charge carriers and reduces electron-hole recombination in the bulk phase. The face-to-face contact between the two materials can promote the charge transfer across the heterostructure interface, thus improving the electron-hole separation efficiency. The performance and mechanisms of LDH/g-C3N4 photocatalysts in hydrogen production, CO2 reduction, and organic pollutant degradation are analyzed and discussed. Incorporating reduced graphene oxide or Ag nanoparticles into LDH/g-C3N4 heterojunction and fabricating calcined LDH/g-C3N4 composites are effective strategies to further facilitate charge transfer at the interface of LDH and g-C3N4 and improve the absorption capacity for visible light. This review is expected to provide basic insights into the design of 2D/2D LDH/g-C3N4 heterojunctions and their applications in solar photocatalysis. [Display omitted] •The 2D nature of LDHs and g-C3N4 facilitates constructing 2D/2D heterojunction.•Main strategies for constructing 2D/2D LDH/g-C3N4 heterostructure are summarized.•Intimate linkage of LDHs and g-C3N4 is key for high photocatalytic performance.•Ternary LDH/g-C3N4/X and calcined LDH/g-C3N4 can improve photocatalytic efficiency.